Effect of Time and Cycle Number of Hot Water Blanching on the Hardness of Waxy Granola Potato - Setya Budi Muhammad Abduh; Rizki Nugraheni; Sri Mulyani; Ahmad Ni'matullah Al-Baarri; Rafli Zulfa Kamil; Tien Dat Huynh; Alaeldin Mohammed Ahmed Musa; Annisa Fitriati; Condro Wibowo (Journal of Applied Food Technology, 2026)
Texture is an important quality attribute of fried potatoes having the mealy as the common cultivar to use and pre-treated by blanching. Considering the scarcity of the cultivar, the use of the waxy is unavoidable. This study aims to evaluate the effects of cycled blanching on the hardness of waxy Granola potato. The study has been conducted through steps of potato preparation, determination of blanching interval, blanching experiments, texture analysis, and data analysis. Potato dices (1.3 mm in length side) were subjected to water blanching (1:4, w/v) at 90 °C for 1–5 min and 1–5 cycles with an interval of 16 min predetermined from the time required the for internal temperature of dices immediately after blanching to lower to room temperature (approximately 27°C) prior to texture analysis. The results of the study show that depending on the time and cycle number, the hardness of blanched potato ranges from 82.67 to 928.80 g. Increase in hardness of potato (ranges from 534.14 to 928.80 g) was found on the potato mildly blanched, either at the time up to 2 min or cycle number up to 2 and a consistent softening (ranges from 753.00 to 82.67 g) was found on those beyond. Blanching for 1 min and cycled up to 5 consistently increased hardness (534.13–753.00 g), fitting to a linear regression (R2 = 0.97). It can be concluded that both time and cycle number significantly (p<0.05) affect the hardness of blanched potato. Blanching for 1 min and cycled up to 5 is proposed to be exploited in further study in potato frying optimization of Granola potato suggesting that cycled short blanching may serve as a suitable pretreatment strategy for improving the textural quality of the cultivar.